Principales plagas del cultivo de uvilla (Physalis peruviana L.), variedad Colombiana, en la zona de Cumbas Conde, cantón Cotacachi, provincia Imbabura - Saavedra Cumba, Gloria Ximena (2019)
SUMMARY The ignorance of the plagues that attacks the cultivation of the grapevine, has generated great economic losses to the producers of the Quiroga parish, Cotacachi canton, this study was carried out with the purpose of identifying the main pests that attack, damage and lower the production in the cultivation of uvilla in the area. The investigation was made by the method of the surveys that were carried out directly to the farmers of the parish. Once the work was finished, the data tabulation process continued with the following results: It was concluded that the pests with greater incidence in the crop is the flea beetle along with the perforator of fruit and aphids, and finally in regard to weeds it was identified that the kikuyo is the most affected to the crop accompanied by the bledo. In addition, the survey revealed that all farmers in the area use the chemical method to control insects using pesticides, and in relation to weeds it was determined that most producers use physical control. Other important data that could be extracted from the survey is that no farmer in the parish performs an analysis of production cost and that the cultivated variety is the Colombian type eco, which showed that the crops in the area have a high rate of presence of pests which will be affected and have a low production yield. Key words: uvilla, pests, incidence